Wushu: from oriental martial art to western sport (2013)
At first the Wushu was considered an important part of Chinese culture and philosophy and although it still is for many, it is now more a sport, with its rules and even world federation. The article briefly describes its history, what it meant for the Chinese and what it is now for the world. This article exposes the author's opinion about the change he has had regarding its beginnings and why it should not be so.